Alteration of Gene Expression in Normal-Appearing Colon Mucosa of APC min Mice and Human Cancer Patients - Ling‐Chun Chen; Chunyi Hao; Yanek S. Y. Chiu; Patrick Wong; Jane Melnick; Martin Brotman; John C. Moretto; Fredrick Mendes; Andrew Smith; James L. Bennington; Dan H. Moore; Nancy M. Lee (2004)
Abstract The expression of many genes is altered in colon cancer, but the roles of these genes in carcinogenesis are unclear. Using real-time quantitative PCR, we demonstrated that several genes previously implicated in human colon cancer undergo altered expression in the APCmin mouse adenomatous polyp, a precursor of cancer, as well as in normal-appearing surrounding mucosa. The five genes that were most highly up-regulated in mouse polyp were also significantly up-regulated in polyp-free colon mucosa. Similar changes occurred in morphologically normal mucosa of surgical sections taken from human cancer patients, frequently extending to the margins. Thus, morphologically normal colon mucosa in APCmin mice and in human cancer patients is not metabolically normal. Altered gene expression in this tissue does not appear to result from a field effect because there was no correlation between extent of altered regulation and distance from polyp or tumor. Our data suggest that alterations of expression levels of these genes may be an early event in carcinogenesis and a marker of risk for the development of colon cancer.